Morphometric Study of Several Species of the Genus Jatropha Linn. (Euphorbiaceae) - Opeyemi Saheed KOLAWOLE (Notulae Scientia Biologicae, 2016)
Morphological parameters of several Jatropha species, namely Jatropha curcas L., Jatropha gossypifolia L., Jatropha podagrica Hook., Jatropha integerrima Jacq. and Jatropha multifida L. were subjected to quantitative analysis within the present study. Twelve traits of the leaves, fruits and seeds were analysed: leaf length, leaf width, leaf length/width ratio, petiole length, petiole width, fruit length, fruit width, fruit length/width ratio, seed length, seed width, fruit stalk length and fruit stalk width were subjected to Principal Component Analysis (PCA) and cluster analysis. Highly significant positive correlations have been noted, while negative correlation was observed between leaf width and leaf length/width ratio, fruit width and leaf length/width ratio. Traits such as leaf length, leaf width and leaf length/width ratio contributed significantly along with other traits to discriminate the studied Jatropha species.  J. podagrica and J. integerrima were found to have more similarities, with a stronger coefficient of agglomeration (69.072) than J. curcas and J. podagrica with 315.028 coefficient of agglomeration respectively. The generated dendrogram showed the relationship between the studied Jatropha species, whereas great affinity was noted between J. podagrica and J. multifida as compared with J. gossypifolia and J. integerrima which are distantly related. The closeness observed between J. podagrica and J. multifida is in line with their current sub-generic grouping.